1)  The answer is: [B]: r = 5 .
__________________________
Explanation:
__________________________ 
Given: 7r − 7 = 2r + 18 ; Round your answer to the nearest tenth, if necessary.
____________________________
Since “r” is the only variable given, let us assume we want to solve for “r” (instead of “x”).
___________________________
→ Subtract “2r” from EACH SIDE of the equation; and & add “7” to EACH SIDE of the equation:
_____________
→ 7r − 7 − 2r + 7 = 2r + 18 − 2r + 7 ;  to get: → 5r = 25 ;
_____________
→ Now, divide EACH SIDE of the equation by “5”; to isolate “r” on one side of the equation; and to solve for “r” :
______________
→ 5r / 5 = 25 / 5 → r = 5 → which is: “Answer choice: [B]”.
_________________
Let us check our answer, by plugging in “5” for “r” in the original equation:
_________________
 → 7r − 7 = 2r + 18 ;  →  7(5) − 7 =? 2(5) + 18? ;
______________________
→ 35 − 7 =? 10 + 18 ?;     → 28 =? 28? Yes!
______________________
 2) The answer is: [D]: x = 2 .
_____________
Explanation: 
_____________
Given: 2x + 12 = 18 − x ; Solve for “x” (round to nearest tenth, if necessary).
_______________
→ Add “x” to EACH SIDE of the equation, & subtract “12” from EACH SIDE of the equation:  → 2x + 12 + x − 12 = 18 − x + x − 12 ; 
______________
→ To get: 3x = 6 ;  → Divide EACH SIDE of the equation by “3”;
to isolate “x” on one side of the equation; and to solve for “x”:
_____________
→ 3x / 3 = 6 / 3 ; → x = 2 ; which is: “Answer choice: [D]”.
______________
Let us check our answer, by plugging in “2” for “x” in the original equation:
________________
→ 2x + 12 = 18 − x ; → 2(2) + 12 =? 18 − 2 ?
________________
→ 4 + 12 =? 18 − 2 ? ;   → 16 =? 16?  Yes!
________________________________
3)  The answer is: [A]: x = -3 . 
_____________
Explanation:
________________
Given:  8x − 3 = 15x + 18 ; Solve for “x”. Round your answer to the nearest tenth, if necessary.
_________________
→ Subtract “8x” from EACH SIDE of the equation, & add “3” to EACH SIDE of the equation:
_______________
→ 8x − 3 − 8x + 3 = 15x + 18 − 8x + 3 ; to get:
_______________
→ 0 = 7x + 21 ; → Subtract “21” from EACH SIDE of the equation;
_______________
→ 0 − 21 = 7x + 21 − 21 ; to get:
_______________
→  -21 = 7x ; Now divide EACH SIDE of the equation by “7”;
    to isolate “x” on one side of the equation; & to solve for “x”:
_______________
→ = -21 / 7 = 7x / 7 ; →  -3 = x ; which is “Answer choice: [A].”
_________________
Let us check our answer, by plugging in “-3” for “x” in the original equation:
________________
→  8x − 3 = 15x + 18 ;  → 8(-3) − 3 =?  15(-3) + 18 ?;
________________________
→ -24 − 3 =?  -45 + 18 ? ;   →  -27 =? -27?  Yes!
___________________________
4)  The answer is: [C]: y = 11 .
_____________
Explanation:
____________
Given: 6y − 6 = 4y + 16 ; Solve for “y”; Round to the nearest tenth, if necessary.
____________
(Note: Since “y” is the only variable given; assume we are to solve for “y” instead of “x”).
____________
→ Subtract “4y” from EACH SIDE of the equation, & add “6” to EACH SIDE of the equation; → 6y − 6 − 4y + 6 = 4y + 16 − 4y + 6 ; to get:
_______________
→ 2y  = 22 ; Now, divide EACH SIDE of the equation by “2”; to isolate “y” one side of the equation; and to solve for “y” ;
_______________
→ 2y / 2 = 22 / 2 ; →  y = 11 → which is “Answer choice: [C]”.
_______________________________
Let us check our answer, by plugging in “11” for “y” in the original equation:
___________________
→  6y − 6 = 4y + 16 ; → 6(11) − 6 =? 4(11) + 16 ?
_______________________
→ 66 − 6  =? 44 + 16 ?  → 60 =? 60 ?  Yes!
__________________
5)  The answer is: [B]: x = -11 .
_____________________
Explanation:
_________________
Given: 3(x − 4) = 5(x + 2) ; Solve for “x”. Round to the nearest tenth, if necessary.
___________
→Note the “distributive property of multiplication”: 
_____________
a*(b + c) = ab + ac ;  and: a*(b − c) = ab − ac ;
_______________
→ Let us expand EACH SIDE of our given equation.
→Start with the “left-hand side”:
____________
3(x − 4) = (3*x)  − (3*4) = 3x − 12;
______________________________
→Now let us expand the “right-hand side” of the given equation:
____________
→  5(x + 2) = (5*x) + (5*2) = 5x + 10 ;
______________
→Now, we can rewrite the original equation:
_______________
→ 3(x − 4) = 5(x + 2) ; by substituting the expanded values for EACH SIDE of the question:   →  3x − 12 = 5x + 10 ;
__________________
→ Subtract “3x” from EACH SIDE of the equation; and add “12” to EACH SIDE of the equation: →  3x − 12 − 3x + 12 = 5x + 10 − 3x + 12 ; to get:
________________
→  0 = 2x + 22;  → Now subtract “22” from EACH SIDE of the equation:
______________
→  0 − 22 = 2x + 22 − 22 ; to get:  →  -22 = 2x ;
__________
→ Divide EACH SIDE of the equation by “2”; to isolate “x” on one side of the equation; & to solve for “x” ;
_____________
→  -22 / 2 = 2x /2 ;  →  -11 = x ; which is “Answer choice: [B]”.
______________
Let us check our answer, by plugging in “-11” for “x” in the original equation:
___________
→ 3(x − 4) = 5(x + 2) ; →  3(-11 − 4) =? 5(-11 + 2) ? ; 
_______________________
→3(-15) =? 5(-9) ? ; → -45 =? -45 ?  Yes!
_____________________________________________
Hope these answers and explanations are helpful. Best of luck!